2014
DOI: 10.1155/2014/610767
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Pathologic Changes of the Upper Gastrointestinal Tract in Crohn’s Disease

Abstract: Background. Crohn's disease (CD) may involve any part of the gastrointestinal tract. We assessed the prevalence and features of upper gastrointestinal (UGI) lesions in CD. Methods. This was a retrospective study that included 138 CD patients that underwent esophagogastroduodenoscopy (EGD). The rate of Crohn's specific endoscopic lesions in the esophagus, stomach, and duodenum was assessed, and immunohistochemical analysis was performed. Changes in the UGI lesions were assessed in those who had two or more EGD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 13 publications
0
52
1
2
Order By: Relevance
“…The detection rate showed significant differences in each report [21,31,48]. Hirokawa et al reported that the prevalence of granuloma in histologic specimens obtained from lesions with the bamboo-joint-like appearance in the stomach of CD patients was 14.3% [34], which was less than the prevalence in our results (45.5%) [33].…”
Section: Gastric Lesionscontrasting
confidence: 66%
See 4 more Smart Citations
“…The detection rate showed significant differences in each report [21,31,48]. Hirokawa et al reported that the prevalence of granuloma in histologic specimens obtained from lesions with the bamboo-joint-like appearance in the stomach of CD patients was 14.3% [34], which was less than the prevalence in our results (45.5%) [33].…”
Section: Gastric Lesionscontrasting
confidence: 66%
“…According to previous reports, the frequency of esophageal lesions in CD patients ranges from 0.2 to 6% [18][19][20][21]. They are detected less frequently than gastric or duodenal lesions.…”
Section: Esophageal Lesionsmentioning
confidence: 95%
See 3 more Smart Citations